Perlakuan Akuntansi Piutang Serta Seberapa Besar Pengaruhnya terhadap Laporan Keuangan - Indari Umayah; Aqnes Dwi Sakti Hamidah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Uncollectible receivables have a considerable risk and can reduce the level of company profitability. Therefore, every company needs to pay special attention to the management of receivables so as not to cause losses. One of the appropriate methods for recording bad debts in the financial statements is the reserve method. Therefore, the company forms a reserve based on estimates of receivables that are estimated to be uncollectible. The purpose of this study is to evaluate the way accounting treats receivables and how this impacts the financial statements. Using primary data, this research was conducted at KOPERINDO JATIM Kandat, which is located at Jl. Raya Kediri, Kandat Village, Kandat District, Kediri Regency, East Java 64173. Quantitative descriptive analysis was used to analyze the data. The results of the analysis show that, using the percentage of sales approach, the total amount of bad debts will reach Rp23,272,860 in 2024. In contrast, using the reserve method with the percentage of receivables approach, the amount of bad debts will reach Rp120,669,520 in 2024. Based on these results, the calculation of the reserve method with the percentage of receivables approach is in accordance with the theory, which aims to add the amount of accounts receivable to the total receivable.